2005
DOI: 10.1007/s00125-005-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-esterified fatty acid concentrations are independently associated with hepatic steatosis in obese subjects

Abstract: Aims/hypothesis: We tested the hypothesis that NEFA concentrations are higher in obese subjects with fatty liver than in obese subjects without fatty liver. Materials and methods: We recruited 22 obese (BMI>30 kg/m 2 ) men aged 42-64 years, in whom liver fat was assessed by ultrasound and classified into categories of no, mild to moderate and severe fatty liver by two independent radiologists. Regional and visceral abdominal fat were assessed by dualenergy X-ray absorptiometry and magnetic resonance imaging, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 47 publications
8
62
0
Order By: Relevance
“…Moreover, the kappa statistic showed excellent agreement between the two radiologists who independently scored the ultrasound scans (see ESM). Since we showed a marked increase in cortisol clearance with fatty liver and individuals with fatty liver are markedly insulin-resistant [10], we investigated the effect of including fatty liver in the regression models. The regression analyses (Table 2) show that fatty liver did not appear to be independently associated with insulin sensitivity when cortisol clearance and a measure of body fatness were included in the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the kappa statistic showed excellent agreement between the two radiologists who independently scored the ultrasound scans (see ESM). Since we showed a marked increase in cortisol clearance with fatty liver and individuals with fatty liver are markedly insulin-resistant [10], we investigated the effect of including fatty liver in the regression models. The regression analyses (Table 2) show that fatty liver did not appear to be independently associated with insulin sensitivity when cortisol clearance and a measure of body fatness were included in the model.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognised that obesity is associated with nonalcoholic fatty liver disease (NAFLD) and obese subjects with NAFLD are markedly insulin resistant [8][9][10], although the explanation for the marked insulin resistance with NAFLD is poorly understood [11]. Specifically, it is uncertain whether abnormal cortisol regulation or metabolism is responsible for the marked insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…For the Steele equations, 65% was used as the effective fraction and 0.22 l/kg as the distribution volume of glucose for calculation of R a and R d [22,24]. Hepatic insulin sensitivity was measured as insulin-mediated suppression of glucose output in the early part of the clamp and was expressed as percentage suppression 60 min after commencing the insulin infusion, when suppression was linear to this time point [25,26].…”
Section: Methodsmentioning
confidence: 99%
“…NEFA were measured in the fasting state and during the OGTT to allow measurement of insulin-mediated suppression of NEFA concentration [25,27,28]. NEFA concentrations were measured in heparinised plasma samples with an autoanalyser (Konelab 20; Thermo Electon, Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…A reduction in activity of these enzymes would result in decreased triglyceride accumulation and a decrease in liver fat. It is also plausible that the more physically active subjects in our study had better cardiorespiratory fitness with better skeletal muscle and cardiac muscle fatty acid oxidation resulting in diminished substrate flux (of fatty acids) to the liver for hepatic triglyceride synthesis [28]. In support of a relationship between higher levels of physical activity and greater cardiorespiratory fitness in NAFLD, a 16 week supervised exercise program to intervene with modest exercise in middle aged patients with NAFLD, showed that not only did liver fat percentage decrease, but also V02 max was improved, by the modest limited duration exercise intervention of 16 weeks duration [23].…”
Section: Interestingly For Both Incident Fatty Liver (Supplementarymentioning
confidence: 93%